Notch interferes with the scaffold function of JNK-interacting protein 1 to inhibit the JNK signaling pathway - Kim, Jin Woo (National Academy of Sciences, 2005)
The transmembrane protein Notch is cleaved by γ-secretase to yield an active form, Notch intracellular domain (Notch-IC), in response to the binding of ligands, such as Jagged. Notch-IC contributes to the regulation of a variety of cellular events, including cell fate determination during embryonic development as well as cell growth, differentiation, and survival. We now show that Notch1-IC suppresses the scaffold activity of c-Jun N-terminal kinase (JNK)-interacting protein 1 (JIP1) in the JNK signaling pathway. Notch1-IC physically associated with the JNK binding domain of JIP1 and thereby interfered with the interaction between JIP1 and JNK. JIP1 mediated the activation of JNK1 induced by glucose deprivation in mouse embryonic fibroblasts, and ectopic expression of Notch1-IC inhibited JNK activation and apoptosis triggered by glucose deprivation. Taken together, these findings suggest that Notch1-IC negatively regulates the JNK pathway by disrupting the scaffold function of JIP1.